WEGENER’S GRANULOMATOSIS WITH ORAL LESIONS AT PRESENTATION - TALIB, Mastura; MOOSA, Fatimah (The ASEAN Journal of Radiology, 2023)
It has long been appreciated that the mouth is the mirror for the rest of the body. Many systemic diseases have oral symptoms, which often coincide with widespread evidence of disease. In some c​ases, however the oral symptoms may be the presenting sign of systemic disease. We report a case of Wegener’s Granulomatosis presented initially as oral lesions.